Characteristics of Thyroid Cancer Patients in Haji Adam Malik General Hospital - Rizka Annisa Harahap; Pimpin Utama Pohan; Sufitni Sufitni (Indonesian Journal of Cancer, 2021)
Background: Thyroid cancer is the most common endocrine cancer, and its incidence has continuously increased in the last three decades all over the world. The national prevalence of thyroid cancer has not been recorded. Sex, obesity, and the size of thyroid nodules are the risk factors for thyroid cancer. The aim of this study is to acknowledge the characteristics of thyroid cancer patients in Haji Adam Malik General Hospital. Methods: This is a cross-sectional study and carried out among 97 patients with thyroid cancer at Haji Adam Malik General Hospital from 2013 until 2015. Secondary data were obtained by consecutive sampling techniques using medical records. The inclusion criteria are all patients diagnosed with thyroid cancer based on histopathological analysis. Data were analyzed descriptively using SPSS in percentage.Results: From 97 patients with thyroid cancer, it could be concluded that thyroid cancer is the most frequently diagnosed in the age group of 55–64 years (32.0%). Females were predominant that attributed to 71.1% than males (28.9%). The majority of thyroid cancer was diagnosed at stage IV (39.2%) with the most common histopathological feature of papillary thyroid carcinoma (46,4%). Thyroid cancer patients are usually found with normal BMI (37.1%) and nodule thyroid found with the diameter of ≥4cm (47.4%).Conclusions: In the 55–64-year age female group, thyroid cancer is most diagnosed at stage IV with papillary thyroid carcinoma. Thyroid cancer patients are usually found with normal BMI and the nodule size of ≥4 cm.